Pengadaan Tempat Sampah Sebagai Wujud Implementasi Untuk Mengurangi Lingkungan Yang Kotor - Syarifa Nadira; Pradja Nur Isnaeini; Nila Salsabila; Helni Anggraini; Pebriandi Pebriandi (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2023)
The lack of land preparation and trash bins in Pulau Kalimanting Village is one of the problems that has occurred so it is necessary to evaluate the prevention of problems that occur so as not to cause diseases that will make people sick. The purpose of this Kuliah Kerja Nyata (KKN) is to find solutions related to environmental pollution problems found in Pulau Kalimating Village at this time. Some of these places are at the State Elementary School 013 Pulau Kalimanting Village, Posyandu, and Lane House. Because of these problems, the right solution is to procure a trash can as a form of implementation to reduce the dirty environment in Pulau Kalimating Village. This report will describe how the trash can functions for the village community so that with these efforts it is hoped that it can increase public awareness about the importance of environmental cleanliness and understand the concept of sorting organic and anorganic waste. The method used is by directly handing over the bins to the school principal, the head of the posyandu, and the lane chairman who will later use the bins properly. This activity was well received and enthusiastic by the community because it was considered as an effort to improve environmental cleanliness in Pulau Kalimanting Village. Thus, this activity is quite effective in overcoming waste piles.